Ultra‐Low Temperature Sintering and Dielectric Properties of SiO2‐Filled Glass Composites. Issue 11 (24th August 2013) - Ju, Kui; Yu, Hongtao; Ye, Lin; Xu, Guangliang
Abstract : Ultra low temperature co‐fired ceramics system based on zinc borate 3ZnO–2B2 O3 (3Z2B) glass matrix and SiO2 filler was investigated with regard to the phase composition, the microstructure and the dielectric properties as functions of the filler content and sintering temperature. The softening temperature of 554°C and the crystallization temperature of around 650°C for the glass were confirmed by Differential Thermal Analysis result. The X‐ray diffraction results show that all SiO2 ‐filled samples were made up of SiO2, α‐Zn(BO2 )2, Zn3 B2 O6 phases. And there was no chemical reaction between SiO2 and the glass during densification. And then the dielectric constant decreased with the increasing content of SiO2 . At the level of 15 wt% SiO2 addition, the composites can be densified at a sintering temperature of 650°C for 30 min, and showed the optimal dielectric properties at 1 MHz with the dielectric constant of 6.1 and the dielectric loss of 1.3 × 10 −3, which demonstrates a good potential for use in LTCC technology.